The Ameliorative Role of Probiotics in 5-fluorouracil Induced Intestinal Mucositis - Alexandra Arcilla Xin Hui Sim; Jia Ying Cheam; Jodi Woan-Fei Law; Vengadesh Letchumanan; Yatinesh Kumari; Satoshi Ogawa; Sunny Hei Wong; Kok-Gan Chan; Loh Teng-Hern Tan (Progress in Microbes and Molecular Biology)
Colorectal cancer (CRC) remains one of the top cancers in the world. Although early detection improves the survival rate to around 90%, late detection would mean the need to use chemotherapy or radiotherapy, especially if surgery is not feasible. 5-fluorouracil (5-FU) is one of the common anti-cancer drugs used in treating CRC. It is the drug that has the greatest efficacy on CRC. Although it improves the survival rate, it has many detrimental side effects. One of these side effects is intestinal mucositis. It is described as having reduced villus height, villus atrophy, crypt fissure, abdominal discomfort, diarrhoea, and weight loss. Clinically, there is no conclusive treatment therapy for mucositis. This is possibly due to the complex mechanism of the pathobiology of intestinal mucositis that includes the production of pro-inflammatory cytokines and increased epithelial cell apoptosis. 5-FU itself is known to cause gut dysbiosis. Current studies revealed probiotics play a role in attenuating this inflammatory process of intestinal mucositis by reversing gut dysbiosis, reducing the expression of pro-inflammatory cytokines, and reducing intestinal damage. This review outlines the latest evidence supporting probiotic use in ameliorating 5-FU induced intestinal mucositis, thereby promoting good health and well-being in colorectal cancer patients receiving 5-FU chemotherapy.